E-modul IPS Kekayaan Budaya Indonesia Berbasis Karakter Toleransi dan Cinta Tanah Air Untuk Kelas IV Sekolah Dasar - Masitha, Amalia Dwi; Sulistyowati, Prihatin; Yulianti, Yulianti (SITTAH: Journal of Primary Education, 2024)
This research is motivated by the limitations of teachers in utilizing technology to develop engaging and effective teaching materials, which impacts students' motivation and understanding of learning. The study aims to produce a valid, practical, and effective character-based IPS e-module. The research employs the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. Data collection involved validation instruments from material, language, and media experts, as well as practicality questionnaires for teachers, student response questionnaires, and pretest and posttest questions. Data analysis utilized both qualitative and quantitative techniques. Subjects included teachers and 20 fourth-grade students from a public elementary school in Malang Regency. Results showed validation scores of 92.3% from material experts, 95% from language experts, and 97.5% from media experts, all categorized as very valid. Teacher practicality was rated at 98%, and student responses at 92.5%, both deemed very practical. Effectiveness, measured by the n-gain test, scored 78.06, indicating effectiveness. These results indicate that the character-based IPS e-module provides engaging material, making it easier for students to understand the content, increasing motivation and learning outcomes, and fostering student character development. The e-module makes learning interactive, with students feeling enthusiastic and actively engaged. The character-based IPS e-module can be used as an innovative learning media by integrating character values, making learning more meaningful.